Whitewashed stories: Tourist narratives of ethnic and social minorities in Buenos Aires - Hruby, Roxana Laura (2024)
This work understands tourism as a communicative operation in which resorting to stories (factual or fictional) is part of the dynamics of social systems (Osorio, 2007; Vázquez et al., 2013). Based on this definition, this study investigated those stories that influence the configuration of Buenos Aires society. The purpose was to analyse and problematise the tourist narratives linked to the ethnic and social minorities that gave rise to Buenos Aires’s identity profile (indigenous, African, enslaved, and gauchos), pointing out its scopes and consequences about the promotion of the city’s tourist image. Methodologically, the article had a qualitative design with a theoretical approach. We reviewed secondary and tertiary sources and direct and participant observations. We conducted a comparative study between the elements described and the analysis of the current cultural offer on the Tourism Entity’s website.